1992
DOI: 10.1002/j.1460-2075.1992.tb05383.x
|View full text |Cite
|
Sign up to set email alerts
|

Three widely separated positions in the 16S RNA lie in or close to the ribosomal decoding region; a site-directed cross-linking study with mRNA analogues.

Abstract: Synthetic mRNA analogues were prepared by T7 transcription, each containing several thio‐uridine residues at selected positions. After binding to the ribosome in the presence of cognate tRNA, the thio‐U residues were activated by UV irradiation and the resulting sites of cross‐linking to 16S RNA analysed. Three distinct cross‐links were consistently observed: (i) from position ‘+6’ of the mRNA (the 3′‐base of the A‐site codon) to base 1052 of 16S RNA; (ii) from position ‘+7’ of the mRNA to base 1395; and (iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 38 publications
9
96
0
Order By: Relevance
“…A1191 (A909) and A1716 (A1413) are among the ''class III'' sites in the 30S subunit that are protected by either binding of tRNA in an mRNA-independent manner, or by binding of the 50S subunit Noller 1986, 1987). In addition, A628 (A532) becomes protected in E. coli 30S ribosomal subunits upon binding of a P-site tRNA and can be directly cross-linked to mRNA (Rinke-Appel et al 1991;Dontsova et al 1992).…”
Section: Wwwrnajournalorg 1901mentioning
confidence: 99%
“…A1191 (A909) and A1716 (A1413) are among the ''class III'' sites in the 30S subunit that are protected by either binding of tRNA in an mRNA-independent manner, or by binding of the 50S subunit Noller 1986, 1987). In addition, A628 (A532) becomes protected in E. coli 30S ribosomal subunits upon binding of a P-site tRNA and can be directly cross-linked to mRNA (Rinke-Appel et al 1991;Dontsova et al 1992).…”
Section: Wwwrnajournalorg 1901mentioning
confidence: 99%
“…sU is a well known cross-linking reagent used in studies of RNA⅐RNA and RNA⅐protein interactions (17). This reagent can be easily incorporated into RNA molecules by in vitro T7-transcription, and incorporation of sU residues does not significantly affect the structure of the RNA molecules nor their biological activity (36).…”
Section: Discussionmentioning
confidence: 99%
“…For the synthesis of sU-modified tmRNA transcripts, UTP was supplemented with 4-thio-UTP at different molar ratios (from 1:1 up to 1:100). The level of 4-thiouridine incorporation was estimated using the T2 fingerprinting technique (17). For example, one or two 4-thiouridine residues per molecule were incorporated at an sU:U ratio of 1:100, and tmRNA transcripts were purified as described for mRNAs (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In bacterial ribosomes, G530 contacts both the second and third base pair of the cognate codon d anticodon complex, facilitating its recognition by the ribosome (for review, see Ogle et al 2003). DNA cross-linking assays showed that only when the A site is empty, G530 lies very close to the mRNA region corresponding to the Ty3 stimulator (Dontsova et al 1992;Rinke-Appel et al 1993). Based on the complementarity and proximity of the mRNA and rRNA, Li et al (2001) predicted that the Ty3 stimulator might pair with this region (Fig.…”
Section: Introductionmentioning
confidence: 99%